Pyrolysis Study of Different Fruit Wastes Using an Aspen Plus Model - AlNouss, Ahmed; Parthasarathy, Prakash; Mackey, Hamish R.; Al-Ansari, Tareq; McKay, Gordon (Frontiers in Sustainable Food Systems, 2021)
Large quantities of fruit wastes are generated during the consumption and processing of fruits. The disposal of fruit wastes in an environmentally benign way is a challenging task. The biochar production from fruit wastes by pyrolysis is receiving huge attention because it can alleviate pollution of fruit wastes and provide a supply of biochar sustainably. In this study, five fruit waste types- orange peel, banana peel, mango endocarp, apricot kernel shell, and date pits are examined. An Aspen plus simulation tool was employed to develop a steady-state model to predict the pyrolysis product yields of the fruit wastes. The details of the proximate and elemental analyses of the fruit wastes were applied as input parameters in the model and the simulation was carried out at 300-600°C and one-atmosphere pressure. Among the fruit wastes, the date pits presented the highest char yield (50.92 wt. %) while the mango endocarp offered the highest syngas yield (54.23 wt. %). From the simulation results, it can be inferred that the date pits are best suited for biochar production whereas the mango endocarp and orange peel are appropriate for syngas generation. The study is further analyzed by studying the optimization of biomass feedstock blend to yield the highest char relative to bio-oil and syngas. The optimization results demonstrate apricot kernel shell and date pits to dominate the feedstock blend. It is hoped that the current outcomes will be helpful in the selection of appropriate feedstocks for biochar generation through pyrolysis.